2016
DOI: 10.1158/0008-5472.can-15-2622
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA Methylation–Independent Epigenetic Events Underlying Clear Cell Renal Cell Carcinoma

Abstract: Alterations in chromatin accessibility independent of DNA methylation can affect cancer-related gene expression, but are often overlooked in conventional epigenomic profiling approaches. In this study, we describe a cost-effective and computationally simple assay called AcceSssIble to simultaneously interrogate DNA methylation and chromatin accessibility alterations in primary human clear cell renal cell carcinomas (ccRCC). Our study revealed significant perturbations to the ccRCC epigenome, and identified gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 42 publications
8
48
0
Order By: Relevance
“…Our goal is to identify “driver” epigenetic events as potential therapeutic targets induced by SGI‐110 that could result in gene expression changes, thereby accounting for alterations of cellular phenotypes upon treatment. Because nucleosome positioning also plays an important role in regulating gene expression, we performed Acce SssI ble analysis to simultaneously analyze DNA methylation and chromatin accessibility in HCC cell lines after SGI‐110 treatment . In this assay, chromatin accessibility levels at individual CpG loci were obtained by subtracting the endogenous DNA methylation β value from the β value after M. Sss I treatment for each probe on the HM450 platform (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal is to identify “driver” epigenetic events as potential therapeutic targets induced by SGI‐110 that could result in gene expression changes, thereby accounting for alterations of cellular phenotypes upon treatment. Because nucleosome positioning also plays an important role in regulating gene expression, we performed Acce SssI ble analysis to simultaneously analyze DNA methylation and chromatin accessibility in HCC cell lines after SGI‐110 treatment . In this assay, chromatin accessibility levels at individual CpG loci were obtained by subtracting the endogenous DNA methylation β value from the β value after M. Sss I treatment for each probe on the HM450 platform (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the Acce SssI ble assay, nuclei preparation and M. Sss I methyltransferase (New England BioLabs) treatments were performed as described . The subsequent Infinium DNA methylation assay was performed at the University of Southern California Molecular Genomics Core Facility according to the manufacturer's specifications (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…The justification for this combination is extensively supported by previous data. In a study from our group, we showed that decreased chromatin accessibility in malignant cells (with a concomitant decrease in gene expression) was only partly associated with increased DNA methylation on the same probes, suggesting that the probes without DNA methylation most possibly obtain the repressive H3K27me3 histone mark (Becket et al ., ). Another study showed that malignant cells can have almost double as many combined DNA methylation and H3K27me3 silencing marks, as compared to normal cells (Takeshima et al ., ), further supporting treatment strategies that combine inhibition of DNMT1 and EZH2.…”
Section: Discussionmentioning
confidence: 97%
“…Prewarmed (37 °C) 300 μL Stop Solution [10 mmol·L −1 Tris/HCl (pH 7.9), 600 mmol·L −1 NaCl, 1% SDS, 0.1 mmol·L −1 EDTA] and 3 μL Proteinase K (20 mg·mL −1 ) were added to each tube, and each reaction mixture was incubated at 55 °C for 16 h. The DNA was then purified by phenol/chloroform extraction and ethanol precipitation and finally redissolved in 21 μL nuclease‐free water for the subsequent analyses. One microgram of DNA was bisulfite‐converted using the Zymo EZ DNA Methylation Kit, and subsequent quality control of M.SssI treatment was performed as previously described (Becket et al ., ), using ACTB, C1D, and GRP78 as controls. The primer sequences are given in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Of great interest is the difference in fetal liver expression of DNA methylation‐responsive genes by season, however, these data were unexpected, as the DNA methylation ratios would have suggested greater transcription activity in fetal livers derived from summer breedings. Methylation of gene regulatory regions is commonly associated with reduced gene expression, however, growing evidence has demonstrated that this is not always the norm (Becket et al, ; Ke et al, ). Although the results were unexpected, these data are in line with what was observed in the placental tissues.…”
Section: Discussionmentioning
confidence: 99%